2005
DOI: 10.1111/j.1440-1754.2005.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Physician counselling practices and decision‐making for extremely preterm infants in the Pacific Rim

Abstract: We report physician beliefs and practices regarding resuscitation and the counselling of parents of extremely preterm infants in Pacific Rim countries. While we find variation among countries, physician practices appear to be determined by ethical decision-making and medical factors rather than social or economic factors in each country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 16 publications
4
55
1
1
Order By: Relevance
“…They may be at a disadvantage if longterm issues were not addressed prenatally, 88 because their attention is directed toward the immediate effects of interventions without consideration of long-term consequences. 88,89 Unintentionally failing to address the longer-term outcomes and their meaning to families may lead to misperceptions about future expectations.…”
Section: Quality Of Life Versus Sanctity Of Lifementioning
confidence: 98%
See 2 more Smart Citations
“…They may be at a disadvantage if longterm issues were not addressed prenatally, 88 because their attention is directed toward the immediate effects of interventions without consideration of long-term consequences. 88,89 Unintentionally failing to address the longer-term outcomes and their meaning to families may lead to misperceptions about future expectations.…”
Section: Quality Of Life Versus Sanctity Of Lifementioning
confidence: 98%
“…98 Research optimizing risk communication has been limited. The general public's awareness of issues related to extreme prematurity is limited, 89 and is impacted by the way in which information is presented. 107 A series of investigators and parents have advocated for increased education of the general public, especially those who are pregnant, 89 and for consideration of initiatives to create advance directives for pregnancies threatened with preterm delivery.…”
Section: Unique Circumstances: Medical Decision-making During the Prementioning
confidence: 99%
See 1 more Smart Citation
“…(We have subsequently reported birth weight and gestational age thresholds for resuscitation elsewhere. 44 ) The San Francisco cohort had lower birth weights, and the Taiwan cohort had larger birth weights in comparison to the other cohorts (P Ͻ .001). The Taiwan cohort also had higher gestational ages than the Singapore and San Francisco cohorts (P Ͻ .001).…”
Section: Samplementioning
confidence: 99%
“…Some physicians approach the conflict by only offering their preferred treatment. Martinez et al surveyed neonatologists and found highly variable counseling practices, with 10-80% regularly discussing withholding or withdrawing of life support [Martinez et al, 2005].…”
Section: Benefit Vs Burden-who Decides?mentioning
confidence: 99%